2021
DOI: 10.32764/dinamika.v6i2.1872
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Students’ Perspectives on the Use of Tiktok as an Instructional Media in Distance Learning During Pandemic Era

Abstract: Abstract This study aims to investigate on students’ perspective on the use of TikTok Application as supplementary instructional media during pandemic session. 20 students of English Department Student at UNWAHA were voluntary to take part in this descriptive study. Employing questionnaire was carried out to obtain data related to their opinion. The researcher collects the data through questionnaire. Then, the researcher selects and identifies the data. After selecting the data, the researcher displays t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…The qualitative findings of the present study first revealed that the participants held a dichotomy of views on the effectiveness of TikTok use in English learning, with one side supposing that making use of TikTok could assist the development of GEP in general and OEP in particular, in contrast to the other side of students stating that TikTok use was of little effect on their English learning. The latter part of the findings raises a suspicious voice that has not been reported in most previous research, which instead has only presented an affirmative view of students and teachers on the effects of TikTok use [21], [23]. To verify the null hypothesis that TikTok use under the umbrella of MALL could improve English proficiency, a quasi-experimental study was conducted.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The qualitative findings of the present study first revealed that the participants held a dichotomy of views on the effectiveness of TikTok use in English learning, with one side supposing that making use of TikTok could assist the development of GEP in general and OEP in particular, in contrast to the other side of students stating that TikTok use was of little effect on their English learning. The latter part of the findings raises a suspicious voice that has not been reported in most previous research, which instead has only presented an affirmative view of students and teachers on the effects of TikTok use [21], [23]. To verify the null hypothesis that TikTok use under the umbrella of MALL could improve English proficiency, a quasi-experimental study was conducted.…”
Section: Discussionmentioning
confidence: 89%
“…In acknowledgement that the working mechanisms of TikTok can assist learning, researchers have attempted to supplement classroom teaching with TikTok and presented a favourable picture regarding students' and teachers' perception of this application when used appropriately in formal learning contexts [21]- [23]. Meanwhile, the effects of such a combination have also triggered great research interest.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The studies of Porcher (2021), who has also worked with the platform, report that students consider TikTok videos to help develop grammatical competence. Afidah et al (2021) also showed in their studies that almost 90% of their participating population preferred to study with TikTok videos and that these are better for developing linguistic competence than other types of materials. Aziz and Sabella (2021) also conducted a study that showed more progress in students' grammatical competencies when using TikTok as a teaching tool.…”
Section: Attractionmentioning
confidence: 97%
“…One study has shown that students have positive attitudes towards the use of TikTok videos as aids in learning English; it helps catch students' attention and in eliminating their boredom, especially in EFL class because of its many interesting features (Afidah et al, 2021). Moreover, its application got 45 million downloads globally during the three-month period which surpassed Facebook and WhatsApp as the most popular app (Huang, 2018).…”
Section: Introductionmentioning
confidence: 99%